Избирательность рестриктазы BspRI в отношении собственных сайтов на ДНК - Сагитов, В.Р.; Метлицкая, А.З.; Александров, А.А. (Биополимеры и клетка, 1987)
Измерены относительные скорости гидролиза 19 различных сайтов рестриктазы BspRI на плазмидах pBR322, pUC19 и pAOЗ. Найдены особенности окружающих нуклеотидных последовательностей, характерные для сайтов с высокой и низкой скоростями гидролиза. Виміряно відносні швидкості гідролізу 19 різних сайтів рестриктази BspRI на плазмідах pBR322, pUC19 і pAO3. Знайдено особливості оточуючих нуклеотидних послідовностей, характерні для сайтів з високою і низькою швидкостями гідролізу. Relative hydrolysis rates are measured for 15 BspRI sites (GGCC) on pBR322 and pUC19 plasmids and for 4 sites on pAO3 plasmid. Some features of nucleotide sequences in 5'-direction from the site have been found: the sequence CPuT or its part PuT adjacent to the site with high hydrolysis rate; PuPu pair in —1-2 position and/or A in —3 position relative to the boundary of sites with low hydrolysis rate; some combinations of these features, but T always in —1 position for sites with intermediate rates. Relative hydrolysis rates of sites are the same for supercoiled and linear DNAs. An attempt is made to explain these results in terms of peculiarities of local DNA structure near the restriction site.